Os Apinajé E A História. Reflexões Sobre A Historicidade Apinajé Na Documentação Histórica E Na Literatura Antropológica - Santos, Carolina Alvim [UNIFESP] (2018)
This Work Is A Contribution To The Studies Of Indigenous History, Through The Reconstitution Of The History Of The Apinajé And Other Jê Speaking Groups Of The Northern Region Of Tocantins. By Using Colonial Documentation Brought By Historians And, Mainly, The 19th Century Presidential Reports Of The Province, The Research Tries To Reconstruct The Historical Context In Which Indigenous Groups Were Social Actors And Political Agents Of Their Own History. Against An Anthropology That, Since Nimuendajú"S Work, Thinks Apinajé Culture In A De-Historized Way, We Aim To Bring Information And Reflections On The Native Historicity. By This, We Mean The Participation Of The Indigenous Peoples In The Regional And National History, As Well As In The Ability To Choose Material And Symbolic Strategies Of Negotiation With The Surrounding Society.